Strategi Pengembangan Model Klinik Konsultasi Agribisnis dalam Pemberdayaan Petani di Kabupaten Konawe Selatan - Sarinah, Sarinah; Arimbawa, Putu; Mardin, Mardin; Abdullah, Weka Gusmiarty; Adriati, Adriati (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2011)
The research objectives were to determine: (1) the agricultural model development strategy of Agribusiness Consulting Clinic; and (2) the internal and external factors of Agricultural Extension Centers to develop the agricultural extension model of Agribusiness Consulting Clinic. The data collection was conducted in sub-District Ranomeeto Barat, District Konawe Selatan in 2010. The Samples were the extension workers and the key person of the farmer group. The analysis SWOT used to analyze the data to reach the research objective. The results showed that: (1) the strategy that used was to develop the model Agribusiness Consulting Clinic were (a) improving service Agricultural Extension Centers as providers of agricultural technology to increase resource extension, (b) improving crop productivity in the region by making Agricultural Extension Centers as an Agribusiness Consulting Center, (c) improving access to information of agribusiness through farmer group-based approach, and (d) improving education facilities and infrastructure in supporting the implementation of farming technology; and (2) the internal factors consisted of: (a) strength: central government support and farm community, the Agricultural Extension Centers location close to farmland, extension workers who are skilled and experienced, the availability of demonstration garden, and institutional peasant (farmer groups); and (b) weakness: limited of extension means, limited field laboratory, lack of electricity and internet networks, and the lower of farmers participation. While the external factors consisted of (a) opportunities: demands of advanced agricultural technology, market presence of agribusiness product, and horticultural planting areas; and (b) threats: globalization, price instability, lack operational funds and government policy.